Correlation of gene expression of ATP-binding cassette protein and tyrosine kinase signaling pathway in patients with hepatocellular carcinoma - Hoffmann, Katrin; Longerich, Thomas; Büchler, Markus W.; Schemmer, Peter; Lin, Shibo; Xiao, Zhi (Anticancer research, 2011)
Background: Recent evidence suggests an involvement of the tyrosine kinase signaling pathway in the development of ATP-binding cassette (ABC) protein-mediated multidrug resistance in cancer. The aim of our study was to determine the relevance of kinase and multidrug-resistance protein expression in human hepatocellular carcinoma (HCC). Material and Methods: Paired tissue samples of HCC and corresponding peri-neoplastic tissue from 15 patients undergoing surgical resection were analyzed. The gene expression of ABC proteins and mitogen-activated protein kinase (MAPK) signaling cascade kinases was evaluated by real-time PCR and correlated with a series of clinicopathological parameters. In vitro effects of MAPK Kinase (MEK) inhibition were evaluated in HepG2 cells. Results: Overexpression of ABC proteins, tyrosine kinases, or both was detectable in 40%, 86% and 33% of HCC samples, respectively. ABCC1, -2 and -3-mRNA levels were significantly increased in 13%, 20% and 33% of the HCC samples compared to the corresponding peri-neoplastic tissue (p≤0.05). There was an association of ABCC1 and ABCC2 overexpression in HCC tissue (p≤0.05). EGFR, RAF, MEK, ERK and MAPK mRNA were overexpressed in 33%, 33%, 40%, 50% and 50%, respectively compared to the peri-neoplastic tissue (p≤0.05). The expression of ABCC1, ABCC2 and P-glycoprotein correlated statistically with the MEK gene expression. Patients with tyrosine kinase overexpression had significantly higher angioinvasion (p≤0.05). RAF overexpression correlated statistically with increased tumor size (p=0.052). In vitro, MEK inhibition led to a reduced ABCC1 mRNA and protein expression. Conclusion: ABC proteins and tyrosine kinases are significantly overexpressed in HCC tissue. The multidrug-resistance phenotype is associated with the MEK expression in HCC. Inhibition of MEK might be a new therapeutic approach to restore chemosensitivity in patients with highly resistant tumors.